A demonstration of the effect of fringe-rate filtering in the hydrogen epoch of reionization array delay power spectrum pipeline - Garsden, Hugh; Bull, Philip; Wilensky, Michael J; Abdurashidova, Zuhra; Adams, Tyrone; Aguirre, James E; Alexander, Paul; Ali, Zaki S; Baartman, Rushelle; Balfour, Yanga; Beardsley, Adam P; Berkhout, Lindsay M; et al. (Monthly notices of the Royal Astronomical Society, 2024)
Radio interferometers targeting the 21cm brightness temperature fluctuations at high redshift are subject to systematic effects that operate over a range of different time-scales. These can be isolated by designing appropriate Fourier filters that operate in fringe-rate (FR) space, the Fourier pair of local sidereal time. Applications of FR filtering include separating effects that are correlated with the rotating sky versus those relative to the ground, down-weighting emission in the primary beam sidelobes, and suppressing noise. FR filtering causes the noise contributions to the visibility data to become correlated in time, however, making interpretation of subsequent averaging and error estimation steps more subtle. In this paper, we describe fringe-rate filters that are implemented using discrete prolate spheroidal sequences, and designed for two different purposes–beam sidelobe/horizon suppression (the ‘mainlobe’ filter), and ground-locked systematics removal (the ‘notch’ filter). We apply these to simulated data, and study how their properties affect visibilities and power spectra generated from the simulations. Included is an introduction to fringe-rate filtering and a demonstration of fringe-rate filters applied to simple situations to aid understanding.